The effect of management capability and entrepreneurial orientation on business performance through business strategy as an intervening variable - Idris Yanto Niode (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
This study aims to analyze and know the role of management capability and entrepreneurial orientation on business performance through business strategy in the micro and small food industry (IMK) in Gorontalo Province. The population is all business people/owners of IMK in Gorontalo Province, with a total sample of 377 respondents. This study applies a non-probability method using purposive sampling and proportionate stratified random sampling techniques. Furthermore, this study uses PLS (Partial Least Square) to analyze the data. The findings show that Management capability has a significant positive effect on business strategy and has a significant positive effect on business performance. Entrepreneurial orientation has a significant positive effect on business strategy and has a significant positive effect on business performance. Business strategy is proven to have a significant positive effect in mediating the effect of management capability and entrepreneurial orientation on business performance. Thus, the theoretical and managerial implication is that all variables involved in this study have a positive and significant direct and indirect influence on business performance. This research is expected to provide understanding and knowledge for Gorontalo food SMEs and local governments in terms of increasing competitive advantage. and IKM business performance can be done through the implementation of entrepreneurial orientation, management skills, and business strategies.